Chloranthaceae endémicas del Perú - León, Blanca (2006)
The Chloranthaceae are represented in Peru by 14 species in the genus Hedyosmum (Brako & Zarucchi, 1993), all of them trees or shrubs. Here we recognize one endemic species, occurring in the Very Humid Montane Forests region, between 1900 and 2650 m elevation. This species has been recorded within Peru’s protected area system.